Comparison of Ground Reaction Forces, Center of Pressure and Body Center of Mass Changes in the Voluntary, Semi-Voluntary and Involuntary Gait Termination in Healthy Young Men - behrooz teymourian; heydar sadeghi; mohammad shariatzade joneydi (Biyumikānīk-i varzishī, 2016)
Objective: The aim of this study was comparing the ground reaction forces, center of pressure and body center of mass changes in voluntary, semi-voluntary and involuntary gait termination in healthy young men.